In depth behavioral phenotyping unravels complex motor disturbances in Cstb−/− mouse, a model for progressive myoclonus epilepsy type 1 - Pollari, Eveliina; Tegelberg, Saara; Björklund, Harry; Kälviäinen, Reetta; Lehesjoki, Anna-Elina; Haapalinna, Antti (Frontiers in Behavioral Neuroscience, 2023)
Progressive myoclonus epilepsy type 1 (EPM1) is an autosomal recessively inherited childhoodadolescence onset neurodegenerative disease caused by mutations in the cystatin B (CSTB gene). The key clinical manifestation in EPM1 is progressive, stimulus-sensitive, in particular action-induced myoclonus. The cystatin B-deficient mouse model, Cstb -/-, has been described to present with myoclonic seizures and progressive ataxia. Here we describe results from in-depth behavioral phenotyping of the Cstb -/-mouse model in pure isogenic 129S2/SvHsd background covering ages from 1.5 to 6 months. We developed a method for software-assisted detection of myoclonus from video recordings of the Cstb -/-mice. Additionally, we observed that the mice were hyperactive and showed reduced startle response, problems in motor coordination and lack of inhibition. We were, however, not able to demonstrate an ataxic phenotype in them. This detailed behavioral phenotyping of the Cstb -/-mice reveals new aspects of this mouse model. The nature of the motor problems in the Cstb -/-mice seems to be more complex and more resembling the human phenotype than initially described.